Tolterodine extended release is well tolerated in older subjects - Griebling, T. L.; Kraus, S. R.; Richter, H. E.; Glasser, D. B.; Carlsson, M. (International journal of clinical practice (Esher), 2009)
Summary Objectives:  To investigate the tolerability of tolterodine extended release (ER) in older subjects with overactive bladder (OAB). Methods:  This was a retrospective analysis of pooled data from five large, randomised, double‐blind, placebo‐controlled trials. Subjects with OAB symptoms, including urinary frequency and urgency (and nocturia in two studies) with or without urgency urinary incontinence, received qd treatment with tolterodine ER (4 mg) or placebo for 8–12 weeks. Data were stratified post hoc by age group: < 65 (n = 2531), 65–74 (n = 1059) and ≥ 75 years (n = 573). Tolerability was assessed by evaluating the occurrence of adverse events (AEs). AE occurrences from each study were mapped to the MedDRA coding dictionary of preferred terms. Results:  Discontinuation rates were slightly higher among subjects ≥ 75 years of age vs. those < 65 years of age; however, this was observed in subjects treated with placebo as well as tolterodine ER. Overall, there were no significant differences in the occurrence of dry mouth, headache, constipation, nausea, urinary tract infection, blurred vision, dry eye, dizziness and micturition disorder in older (65–74 or ≥ 75 years) vs. younger (< 65 years) subjects treated with tolterodine ER relative to placebo (treatment × age; all p > 0.1). Dry mouth was the only AE consistently associated with tolterodine ER treatment (< 65 years, 17%; 65–74 years, 16%; ≥ 75 years, 15%). The occurrence of all other AEs was ≤ 5% in most age and treatment cohorts. Most AEs were mild or moderate in all age and treatment cohorts. Conclusion:  The nature and frequency of AEs associated with tolterodine ER treatment were similar across age groups in subjects with OAB, suggesting that tolterodine ER was not associated with an increased risk of AEs in older vs. younger subjects and, thus, is a suitable first‐line pharmacotherapy treatment for OAB in this population.